Planejamento reverso digital: conceito que o profissional deve conhecer - Oliveira, Cristian Jorge Abram (2018)
The objective of this study was to develop a guidance and clarification of the virtual reverse planning for the dental surgeon who works with dental implants, especially the implant specialists. A folder was developed that describes the clinical and digital steps for the execution of virtual reverse planning. The same was given to the graduate students in implantology at the University of Grande Rio - UNIGRANRIO between June and December 2017 to check their acceptance by professionals. From a total of 36 dental surgeons enrolled in UNIGRANRIO implantology graduate courses, all of them showed good acceptance of the information folder, stating that they did not know the workflow of virtual reverse planning. The main advantage of this type of planning highlighted by the students who received the folder was the possibility of a more faithful and faster visualization of the proposed treatment, guaranteeing the predictability of the treatment. It was also highlighted the fact that virtual reverse planning can be shared among the team professionals through the internet, facilitating the communication of the entire team. The third point, highlighted by 5 students, was the impact on the motivation of the patient in relation to the treatment when the patient can observe the simulation of the final result. It is possible to conclude that virtual reverse planning is an innovative approach that needs to be established in the dental clinic in order to improve communication between patient and team, allowing better prediction of its final result.